2015
DOI: 10.1155/2015/967673
|View full text |Cite
|
Sign up to set email alerts
|

Bone Regulates Glucose Metabolism as an Endocrine Organ through Osteocalcin

Abstract: Skeleton was considered as a dynamic connective tissue, which was essential for mobility, calcium homeostasis, and hematopoietic niche. However more and more evidences indicate that skeleton works not only as a structural scaffold but also as an endocrine organ, which regulates several metabolic processes. Besides osteoprotegerin (OPG), sclerostin (SOST), and Dickopf (DKK) which play essential roles in bone formation, modelling, remodelling, and homeostasis, bone can also secret hormones, such as osteocalcin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 73 publications
1
27
0
6
Order By: Relevance
“…Correspondingly, the cells from healthy donor that exhibited low BSP expression had inferior cell proliferation ability. The OCN was shown to stimulate osteoblast differentiation and osteocyte maturation participating in bone matrix mineralisation (Shao et al, ). The FAM83H mutant cells showed reduced OCN expression while maintained mineralisation ability.…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, the cells from healthy donor that exhibited low BSP expression had inferior cell proliferation ability. The OCN was shown to stimulate osteoblast differentiation and osteocyte maturation participating in bone matrix mineralisation (Shao et al, ). The FAM83H mutant cells showed reduced OCN expression while maintained mineralisation ability.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, insulin, insulin-like growth factor type 1 (IGF1) and incretin hormones have a role in regulating bone homeostasis [2]. The binding of insulin to specific receptors on osteoblast exerts anabolic effects, favoring survival, proliferation and differentiation of osteoblasts [3,8]. More importantly, however, is the mechanism for promoting bone resorption insulin-induced by decreasing the expression of osteoprotegerin (OPG) in the osteoblast favoring the osteoclasts function [1,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The binding of insulin to specific receptors on osteoblast exerts anabolic effects, favoring survival, proliferation and differentiation of osteoblasts [3,8]. More importantly, however, is the mechanism for promoting bone resorption insulin-induced by decreasing the expression of osteoprotegerin (OPG) in the osteoblast favoring the osteoclasts function [1,7,8]. During bone resorption, osteoclasts generate an acidic pH at resorption lacunae level, making it a suitable environment for stored osteocalcin decarboxylation in the bone matrix, allowing it to enter the systemic circulation [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Animal's models have shown that the lack of osteoblasts has been associated not only to alterations on bone density but also to impaired glucose metabolism, such as high blood glucose, low insulin secretion, and insulin resistance The administration of OC can restore glucose and insulin level in circulation but only partially the insulin sensitivity [23][24][25]. In our study, we also observed an association between OC levels and Beta-CTx with insulin resistance, as it has been reported in obese subjects [17,22].…”
Section: Discussionmentioning
confidence: 99%